Internal mechanisms of corporate governance and the likelihood of financial statements fraud: A study from Indonesian public listed companies - Zainal, A.; Muhamad, R. (2014)
This study investigates the impact of internal mechanisms of corporate governance and the likelihood of financial statements in Indonesian public listed companies (PLCs). The findings resulted from a logit regression analysis on a matched pair sample of 47 fraud companies and 47 no-fraud companies from 2007-2012 indicate that fraud is more likely occur in a company having CEO and BOD members bound by a family relationship. In contrary, these results suggest that the likelihood of financial statements is lower when there is at least one financial/accounting/auditing expert in audit committee (AC) member. It also suggests that when number of independent AC member increases, the likelihood of financial statements decreases. These results provide direct implications in further strengthening the internal structure of corporate governance in this emerging market country.